The effect of PEO/NaCl dual porogens in the fabrication of porous PCL membranes via a solid-state blending approach - Rula M. Allaf (Scientific Reports)
Abstract In this investigation, the influence of a combination of poly(ethylene-oxide) (PEO) and salt (NaCl) as water-soluble porogens on the synthesis of sustainable porous poly(ε-caprolactone) (PCL) membranes is explored. Nine mixture compositions are examined. PCL sheets are fabricated through the cryomilling, hot pressing, and porogen leaching approach. The resulting sheets are investigated for their morphologies, porosities, water uptake, and mechanical properties. Thick sheets display a porous lamellar structure with porosities ranging from 47.4% to 70.8%. Lamellae exhibit various surface features ranging from smooth surfaces, rough with pinholes, globular, fibrillar, and finally skeletal structures. Higher salt contents result in more compact lamellae with higher interconnected porosities on the lamellae surfaces. Samples demonstrate significant water uptake, increasing with higher porosities, while mechanical properties decrease. Regression analysis is used to fit the mechanical properties of the thin sheets, revealing second order polynomial functions of porosity. Additionally, the sandwich method is successfully employed to create porous membrane surfaces, yielding various distinct morphologies, including a notable feather-like layered structure and a hierarchal particulate structure with large particles coated with aggregates of tiny particles. These findings contribute to understanding the synthesis and properties of sustainable porous polymer membranes, with implications for various applications.